A Blind Spot in the Diagnostic Field: The Challenging Diagnosis of Tumefactive Multiple Sclerosis - Ramy Mando; Emile Muallem; Shaiva G. Meka; Ramona Berghea (Case Reports in Neurological Medicine)
Tumefactive Multiple Sclerosis (TMS) is a rare variant with 1 per 1000 cases of MS and 3 per million cases per year. TMS can mimic clinical and radiological features of a neoplasm, infarction, or abscess and therefore can be diagnostically challenging for clinicians. We present a clinical scenario of a patient presenting with left homonymous hemianopia with atypical radiological features initially thought to be more consistent with neoplasm or infraction. Ultimately, biopsy was done which led to the diagnosis of tumefactive multiple sclerosis.